Competition and Scope of Activities in Financial Services - Claessens, Stijn (Washington, DC: World Bank, 2014)
This article analyzes the costs and benefits of different degrees of competition and different configurations of permissible activities in the financial sector and discusses the related implications for regulation and supervision. Theory and experience demonstrate the importance of competition for efficiency and confirm that a competitive environment requires a contestable system meaning one that is open to competition-but not necessarily a large number of institutions. A competitive banking system can improve the distribution of consumer credit, enhance the corporate sector's access to financing, and mitigate the risks of financial crises. In an open market, in which services and products are provided in response to market signals, financial institutions respond by offering a wider scope of financial services. The optimal institutional design for supervisory functions is less obvious. This article reviews alternative frameworks for financial services markets from an economic perspective using experiences in several countries as a guide. Authors focus first on the role of competition in the financial sector and the tradeoffs between competition on the one hand and stability and innovation on the other. Authors next examine alternative structures of financial services dictated in many countries.